Continental Strategic Framework to Strengthen Cross-Border Surveillance, Coordination and Information Sharing in Africa - Ms Mallion Kangume; Miss Emily Atuhaire; Dr Joy Ebonwu; Dr Jianglan White; Ms Tina Sorensen; Mr Timothy Wesonga; Dr Merawi Aragaw (International Journal of Infectious Diseases)
Introduction: Africa CDC is a continental autonomous health agency of the African Union with the mandate to support public health initiatives of Member States and strengthen the capacity of their public health institutions to detect, prevent, control and respond quickly and effectively to disease threats. Africa reports the heaviest burden of public health emergencies globally. In the past 22 years, over 100 public health events were reported annually, predominantly infectious (92%) and zoonotic diseases (30%) coupled with humanitarian crises (5%). The incidence of zoonotic diseases continues to increase significantly among countries with similar geographical and epidemiological profiles, leading to cross-border spill overs of outbreaks. Africa CDC developed the continental strategic framework for strengthening cross-border surveillance coordination, collaboration, and information sharing in Africa to address cross-border health threats in the continent. Methods: Africa CDC developed this strategic framework through a participatory and consultative process in collaboration with representatives of regional economic communities (RECs), regional and country stakeholders from African Union Member States, and experts in port health surveillance. Technical input from international partners including the US CDC, IOM, WHO, and UKHSA was also obtained through technical working group sessions. In October 2022, a continental consultative workshop on cross border surveillance and coordination with a representation from 50 AU member states and four regional economic communities (RECs) was held in Kigali, Rwanda. From the workshop, a technical working group with MS representatives from the 5 AU regions, RECs, Africa CDC and technical partners was established to guide the framework development. Among the key performance indicators include number of member states supported to develop Cross-border coordination mechanisms. A detailed implementation roadmap coupled with a robust monitoring and evaluation matrix anchors this framework. Results: The framework fosters partnerships and collaborations that support countries in implementing cross-border surveillance (CBS) initiatives and key interventions, including establishing border health committees, developing SOPs and guidelines, joint action plans, and holding regional trainings, especially during outbreak responses. To date, the framework has supported various notable outbreak responses through the development process, like Ebola Virus Disease (EVD) 2022-2023 in Uganda and Marburg Virus Disease (MVD) in 2023 in Equatorial Guinea and Tanzania. Discussion: This strategic framework is intended for use by National Public Health Institutes, Ministries in charge of human, animal and environmental health, trade, immigration, foreign affairs and other relevant Ministries, departments, organizations, agencies, and sectors involved in border health activities, academia and other stakeholders, including non-state actors to build CBS capacity with MS and to support early detection, prevent and timely response to the public health threats in the continent. Conclusion: This CBS framework is aligned with the Africa CDC Strategic Plan (2023-2027)’s strategic priorities and its ambitious vision of a New Public Health Order for Africa.